2014
DOI: 10.4184/asj.2014.8.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-Related Complications and Sequelae in Management of Tuberculosis of Spine

Abstract: Study DesignMedical record-based survey.PurposeTo survey the overall incidence of the intra- and postoperative complications and sequelae, and to propose the preventive measures to reduce complications in the spinal tuberculosis surgery.Overview of LiteratureThere is no study focused on the surgery-related complications and sequelae, with some touching lightly on the clinical problems.MethodsThere were 901 patients in this study, including 92 paraplegics. One hundred eighty-six patients had no visible deformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…[8][9][10] These techniques take a one-stage correction for spine deformity, and undoubtedly increase surgicalrelated complications, such as large-vessel injuries, neurological injuries (cord, roots, nerves), dural tears, and stabilization failure. 11 Halopelvic traction corrects spinal deformities successfully, since be demonstrated. 1 But it is not popular recently for its shortcoming.…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] These techniques take a one-stage correction for spine deformity, and undoubtedly increase surgicalrelated complications, such as large-vessel injuries, neurological injuries (cord, roots, nerves), dural tears, and stabilization failure. 11 Halopelvic traction corrects spinal deformities successfully, since be demonstrated. 1 But it is not popular recently for its shortcoming.…”
Section: Discussionmentioning
confidence: 96%
“…However, in both of these cases the cause was attributed to a pre-existing intradural-extramedullary tuberculoma with concurrent arachnoiditis. Moon et al [3] in one of the largest studies on surgery-related complications of spinal tuberculosis did not report a single case of post-operative syrinx formation.…”
Section: Discussionmentioning
confidence: 99%
“…For such patients, surgical spinal decompression along with anti-tubercular drug therapy is the usual mode of management. However, lack of neurological recovery or even further neurological deterioration can occur in around 10% of such patients after surgical spinal decompression [3]. Neurological deterioration in these patients can be due to inadequate decompression, multi-drug resistant organisms, physical damage to the spinal cord, or damage to the vascular supply of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…al. (35) , in their study on 901 patients who underwent spinal tuberculosis surgery, reported increasing of the corrected kyphosis angle (32%) and graft failure (14%) as the most common complications associated with the disease. In the same study, thoracic cavity complications (43%), thrombophlebitis (26%) and sympatheticolysis symptoms (32%) were reported as surgical complications, especially in the anterior approach.…”
Section: Grade Of Paraplegiamentioning
confidence: 97%